Network Planning Method and Simulation Analysis for Large-Scale Low Earth Orbit Satellite Constellation Networks - Lixiang LIU; Shuaijun LIU (天地一体化信息网络)
Thanks to the advantages of global coverage, high capacity and low latency, the large-scale LEO satellite constellation networks has become a hot spot for global development.However, planning methods and simulation modeling research for LS-LEOSCN has not been well studied.This paper focused on the following two issues, namely how to evaluate a given LSLEOSCN, and how to design or optimize a constellation network.Three key indicators for evaluating the performance of LSLEOSCN were established, namely network coverage (CT), system throughput (ST) and round-trip time (RTT).Further, the satellite constellation deployment (SCD), gateway station deployment (GSD) were analyzed and designed in the integrated network evaluation and planning (NEaP) platform for LS-LEOSCN.The simulation results showed that the designed NEaP platform could support the development of LS-LEOSCN evaluation and planning.